The Clay Mineral Studies of the Khewra Sandstone Exposed at Khewra, Eastern Salt Range - Baqri, S.R.H.; Rajpar, A.R. (Journal of Himalayan Earth Sciences, 1991)
Detailed investigations were conducted to understand clay mineral composition of the Khewra Sandstone exposed at Khewra Gorge, Salt Range. Oriented clay mineral slides were prepared for X-ray analysis for less than 5 µ fraction. X-ray diffraction studies indicate that the dominant clay mineral in the formation is illite, along with subordinate mixed layer clays in the Khewra Sandstone. Experimental studies indicate that mixed layer clay is a random mixture of illite and chlorite of which the latter is the third dominant mineral. These investigations suggest that genetically both illite and chlorite are detrital in nature brought into the depositional basin by erosion of sedimentary and metamorphic source rocks. The origin of the random mixed layer clay mineral has been interpreted as diagenetic. The temperatures and pressures during burial diagenesis were not high enough to create regularity in the random mixture of illite and chlorite.